American Educators and Democratic Educational Principles and Practices - Arief, Armai; Alek, Alek; Raya, Ahmad Thib; Baker, Shirley; Camden-Anders, Sherry (International Journal of Psychosocial Rehabilitation, 2020)
Teaching and modeling democratic principles throughout all educational endeavors play a central, pivotal role in developing a democratic society. A recent investigation of this topic revealed factors and influences regarding the democratic educational practices conducted by American educators. The study employed a qualitative research paradigm that provided descriptive data in the form of words (written and spoken) describing the social behavior of learners in the learning process and the role of educators and administrators in initiating democratic values. A questionnairewas distributed to twelve participants who contributed responses that formed the research data. Survey responses were analyzed and placed into categories that revealed several patterns or themes that facilitated the results. From the analysis of the data, major research findings were determined: First, Education and democracy are linked in American thought and practice. Education helps people prepare to engage and participate actively in all aspects of a democratic society. Second, the importance of education in American democracy is recognized as the wayto a better future. With education, more opportunities are available for improved career options. In a broader sense, for all generations, education is the key to successfully competing locally and globally for work opportunities. Third, the educators who participated in the study explained that democratic values and attributes such as equality, respect for life, justice, freedom, honesty, cooperation, tolerance, responsibility, acceptance of differences, peace, and self-esteem are taught to ensure a democratic society. In conclusion, educators and administrators were identified as persons responsible for promoting democratic values and providing students with a fair and equal opportunity to receive a quality education.